Impact of Health Insurance on Access to Health Services for Mothers and Children in West Africa - Dadjo, Joshua (Université d'Ottawa / University of Ottawa, 2021)
Background The Sustainable Development Goals provides targets that foster greater mobilization of global resources and efforts. SDG Goal 3 Ensure healthy lives and promote well-being for all at all ages, sets targets for the reduction of maternal mortality rates and mortality rates for children under-five. Health insurance coverage is thought to provide access to needed primary services to accomplish these goals. West Africa is the region of the world with the highest burden of disease and it is unclear if insurance coverage does provide needed access to services. The articles within this thesis examine whether or not health insurance provides greater access to primary services for mothers and children, while determining other factors to be considered. Method For the systematic review, we carried out a search on four databases. Eligible studies included mother’s under-five and children in West Africa. The primary outcome was insurance impacting the rate of utilization of services. Data was extracted using standardized form, and methodology was assessed using the Joanna Briggs Institute forms. Our cross-sectional study used DHS data from 10 West African countries. Data was cleaned, weighed and analyzed using Stata. The independent variable was health insurance, and the variable of outcome was making a minimum of four antenatal care visits. Data was analyzed using binary logistic regression and we presented results using crude and adjusted odds ratio at 95% confidence interval. Results The narrative synthesis was chosen for the review. We found that in most study settings, insurance increased access to services. The cross-sectional study found that women with insurance were more likely to make the recommended number of ANC visits than their uninsured counterparts (aOR [95% CI] =1.55 [1.37-1.73]). Socio-economic status also impact access to services. Conclusion Health insurance does increase access to services and should be pursued as a viable long-term policy, but access is still dependent on socio-economic status. Due to the COVID-19 pandemic, burden of disease of the region and systems challenges, other solutions should be pursued in the near-term. Future investigation should consider the role of equity as a guiding principle.
Keywords: Mother; Children; Insurance; Health Service; West Africa; Health expenditure; Sustainable Development Goal; Health coverage